2005
DOI: 10.1158/0008-5472.can-04-4221
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific pRB Loss Results in Ectopic Cell Cycle Entry and Aberrant Ploidy

Abstract: The liver exhibits an exquisitely controlled cell cycle, wherein hepatocytes are maintained in quiescence until stimulated to proliferate. The retinoblastoma tumor suppressor, pRB, plays a central role in proliferative control by inhibiting inappropriate cell cycle entry. In many cases, liver cancer arises due to aberrant cycles of proliferation, and correspondingly, pRB is functionally inactivated in the majority of hepatocellular carcinomas. Therefore, to determine how pRB loss may provide conditions permiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 65 publications
9
97
1
Order By: Relevance
“…In good agreement with the epidemiologic observations, mice with a liver-specific ablation of the Rb gene showed aberrant ploidy and increased multiplicity of liver tumors when exposed to DEN (Mayhew et al 2005;Mayhew et al 2007;Srinivasan et al 2007). To explore the role of AHR/RB/TGF-β interactions in liver tumorigenesis, we have examined the expression status of Tgfb genes, tumor suppressor genes, Ahr and several of its downstream targets in DEN-induced liver tumors and normal livers of mice with a liver-specific ablation of the Rb gene and in their wild-type littermates.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In good agreement with the epidemiologic observations, mice with a liver-specific ablation of the Rb gene showed aberrant ploidy and increased multiplicity of liver tumors when exposed to DEN (Mayhew et al 2005;Mayhew et al 2007;Srinivasan et al 2007). To explore the role of AHR/RB/TGF-β interactions in liver tumorigenesis, we have examined the expression status of Tgfb genes, tumor suppressor genes, Ahr and several of its downstream targets in DEN-induced liver tumors and normal livers of mice with a liver-specific ablation of the Rb gene and in their wild-type littermates.…”
Section: Introductionsupporting
confidence: 85%
“…Genotypes were determined by standard PCR of tail DNA and deletion or retention of the Rb gene was confirmed by genotyping the mouse livers themselves. Characterization of these tumors has been reported elsewhere (Mayhew et al 2005;Mayhew et al 2007;Srinivasan et al 2007). …”
Section: Micementioning
confidence: 93%
See 1 more Smart Citation
“…Duplicate samples of saponin-permeabilized isolated adipocytes were stained with PI and analyzed by flow cytometry for GFP and DNA content to assess the nuclear ploidy as an indicator of cell fusion events (19). Flow cytometric analysis with singlet discrimination demonstrated that 0.5%-1.5% of the GFP + adipocyte population displayed multinuclear content characteristic of increased nuclear ploidy or putative cell fusion events (Figure 4).…”
Section: Figurementioning
confidence: 99%
“…RB has also been shown to have a crucial role in the maintenance of the quiescent state (Sage et al, 2003). Acute inactivation of RB in adult liver using conditional targeting shows that RB loss alone results in the deregulation of E2F regulatory genes, and induces senescent or quiescent hepatocytes to re-enter cell cycle progression (Mayhew et al, 2005). In addition to G1/S regulation, recent analysis using a microarray shed light on G2-M regulation by the RB/E2F pathway.…”
Section: Introductionmentioning
confidence: 99%